A comparison of tourism PhD Students' publication records and university of study. (July 2017) - Carr, Neil; Hayes, Stu
Abstract: To gain a faculty position at a tertiary education institution, PhD students arguably need to have a publication track record prior to graduation. This paper provides insights into the universities where tourism PhD students are most likely to have such a record. The data utilised includes the publication records of all PhD students at the time of their joining Trinet between mid-March 2007 and mid-July 2015. The data shows that students at some universities are more likely to have developed a publication track record than those at other universities. In addition, students in some universities are disproportionately represented among the publications in high category journals. Highlights: Versities in terms of propensity of PhD students to publish. These include Hong Kong Polytechnic, University of Otago, and Temple University. They may provide examples of best practice to develop students' publication records.